Drilling fluid system capable of improving formation plugging and collapse prevention capacity and preparation method thereof

By using a combination of graded inorganic micro-nanoparticles and asphalt anti-collapse agent in the drilling fluid, a dense mud cake structure is formed, which solves the problem that existing drilling fluid cannot effectively seal shale micropores and cracks, and improves the stability of the well wall and the anti-collapse capability.

CN119899646APending Publication Date: 2025-04-29PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311408064.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing drilling fluid system cannot effectively seal the micropores, microcracks and stratigraphic structures in shale, resulting in instability and collapse of the well wall.

Method used

A drilling fluid system is adopted that combines inorganic micro-nano particles with different particle sizes with asphalt anti-slump agents. By forming a stable dense mud cake structure, pressure is prevented from being transmitted to the cracks and the crack expansion resistance is improved.

Benefits of technology

It effectively improves formation conditions, prevents the well wall from collapse and blocking, maintains the stability of the well wall, and improves the blocking and anti-collapse capabilities of drilling fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899646A_ABST
    Figure CN119899646A_ABST
Patent Text Reader

Abstract

The invention discloses a drilling fluid system for improving stratum plugging and anti-sloughing capacity and a preparation method. The drilling fluid system comprises the following components in parts by weight: 90 parts of white oil, 10-20 parts of CaCl2 saline water, 2.5-4 parts of organic soil, 3-5 parts of an emulsifier, 2.5-4 parts of an auxiliary emulsifier, 3-5 parts of a filtrate reducer, 2.5-4 parts of a wetting agent, 2.5-4 parts of quick lime, 2-8 parts of inorganic micro-nano particles, 4.5-6 parts of an asphalt anti-sloughing agent and 15-110 parts of barite. The inorganic micro-nano particles comprise inorganic micro-nano particles I, inorganic micro-nano particles II and inorganic micro-nano particles III, the average particle size of the inorganic micro-nano particles I is 10 [mu] m-53 [mu] m, the average particle size of the inorganic micro-nano rigid particles II is 6.5 [mu] m-18 [mu] m, and the average particle size of the inorganic micro-nano rigid particles III is 1.3 [mu] m-13 [mu] m. The plugging agent has a good plugging effect on micropores, microcracks and bedding structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling mud in the petroleum industry, and in particular to a drilling fluid system for improving the sealing and anti-collapse capability of formations, a preparation method and application thereof. Background Art

[0002] With the transformation and upgrading of my country's industrial structure and the strong demand for clean energy supply, my country's natural gas demand is expected to increase in recent years. In conventional drilling, large sections of mud shale often cause formation block loss, resulting in downhole complexity. In unconventional shale gas drilling, the long horizontal section of the wellbore stability is insufficient, resulting in instability of the wellbore, causing expansion, collapse, drill bit sticking and other downhole complexities, which is a bottleneck affecting the realization of safe and efficient drilling goals.

[0003] There are many factors that cause wellbore instability, including the unique storage space of shale gas, the properties of clay minerals, and the capillary effect and hydraulic splitting effect caused by drilling fluid penetration. Among them, shale pores have a unique structure, and a small amount of filtrate intrusion can significantly increase the pore pressure near the wellbore wall, weakening the effective support of the static liquid column pressure on the wellbore wall, thus causing the wellbore wall to collapse and become unstable.

[0004] The key to maintaining the stability of shale wellbore walls is that the plugging materials can enter micropores, microcracks and bedding structures to form a tight seal and reduce the intrusion of filtrate and the pressure transmission effect. However, the current plugging materials are not ideal for plugging micropores and microcracks, and it is difficult to form a tight seal.

[0005] In view of this, this patent application is filed. Summary of the invention

[0006] The present invention provides a drilling fluid system, a preparation method and an application thereof for improving the sealing and anti-collapse capability of formations, and is used to solve the technical problem that the existing drilling fluid system cannot form a tight seal for micropores, microcracks, bedding and other structures.

[0007] The first object of the present invention is to provide a drilling fluid system for improving the sealing and anti-collapse ability of formations, comprising the following components in parts by weight: 90 parts by weight of white oil, 10 to 20 parts by weight of CaCl2 brine, 2.5 to 4 parts by weight of organic soil, 3 to 5 parts by weight of emulsifier, 2.5 to 4 parts by weight of auxiliary emulsifier, 3 to 5 parts by weight of filtrate reducer, 2.5 to 4 parts by weight of wetting agent, 2.5 to 4 parts by weight of quicklime, 2 to 8 parts by weight of inorganic micro-nano particles, 4.5 to 6 parts by weight of asphalt anti-collapse agent, and 15 to 110 parts of barite;

[0008] The inorganic micro-nano particles include inorganic micro-nano particles I, inorganic micro-nano particles II, and inorganic micro-nano particles III. The average particle size of the inorganic micro-nano particles I is 10 μm to 53 μm, the average particle size of the inorganic micro-nano rigid particles II is 6.5 μm to 18 μm, and the average particle size of the inorganic micro-nano rigid particles III is 1.3 to 13 μm.

[0009] The drilling fluid system provided in the embodiment of the present invention uses graded inorganic micro-nano particles of different particle sizes to cooperate with asphalt anti-collapse agents. According to the characteristics of the crevices of the Longmaxi formation, that is, for underground pores and cracks with a size range of 36nm-88μm, the size of the inorganic micro-nano rigid particles is selected using the 1 / 3 plugging and bridging principle.

[0010] The embodiment of the present invention can form a stable dense mud cake structure between the wellbore and the formation. For underground pores and cracks with a size range of 36nm-88μm, it can prevent pressure from being transmitted to the cracks and increase the crack expansion resistance, thereby effectively improving the formation conditions. At the same time, the present invention strictly controls the content of each component, so that the components can interact with each other so that the prepared drilling fluid can play the best effect during the drilling process, thereby enabling the prepared drilling fluid to improve the ability of the drilling fluid, prevent the well wall from collapsing and losing stability, and maintain the well wall stability, with good application effect.

[0011] In some optional embodiments, the weight ratio of the inorganic micro-nano particles I, the inorganic micro-nano rigid particles II, and the inorganic micro-nano rigid particles III is 1:1-2:1-3. This weight ratio can reduce water loss. In some optional embodiments, the weight ratio of the inorganic micro-nano particles I, the inorganic micro-nano rigid particles II, and the inorganic micro-nano rigid particles III is 1:1.2:2;

[0012] The inorganic micro-nano particles are calcium carbonate particles.

[0013] Inorganic micro-nano calcium carbonate particles are used in the embodiments of the present invention, which are inorganic micro-nano rigid particles and have a beneficial effect on forming a dense mud cake with a stable structure.

[0014] In some optional embodiments, the asphalt anti-collapse agent is a mixture of oxidized asphalt powder having a softening point of 120°C to 140°C and oxidized asphalt powder having a softening point of 140°C to 160°C;

[0015] The asphalt content of the oxidized asphalt powder with a softening point of 120°C to 140°C is 35% to 40%, and the colloid content is 30% to 35%. The asphalt content of the oxidized asphalt powder with a softening point of 140°C to 160°C is 40% to 55%, and the colloid content is 20% to 35%.

[0016] In the embodiment of the present invention, oxidized asphalt is used for anti-collapse, which can soften and deform under certain temperature and pressure. When under sufficiently high temperature and pressure, the asphalt is softened and squeezed into the micro cracks or pores of the shale, bonding the shale together. The asphalt can also cover the surface of the shale to form a dense and tough film, which not only continues the percolation of the drilling fluid filtrate into the interior of the shale, but also plays an ideal barrier effect on the erosion of the drilling fluid flow, thereby blocking the cracks. The two asphalts can greatly improve the plugging effect of the asphalt after mixing; the oxidized asphalt using the above two softening points can be used in an environment with a formation temperature of 120 to 150 ° C, which can soften the asphalt and ensure a better plugging effect; and in terms of plugging, the asphalt particles should be larger, first piled on the mud cake, and then use finer micro-nano particles to fill the finer pores to achieve a better plugging effect. In some optional embodiments, the oxidized asphalt powder with a softening point of 120°C to 140°C is mixed with the oxidized asphalt powder with a softening point of 140°C to 160°C in a mass ratio of 1:2. Setting the mass of the softening point of 140°C to 160°C to be larger can achieve a better plugging effect. In some optional embodiments, the fluid loss reducer includes a modified fatty acid fluid loss reducer, and the modified fatty acid fluid loss reducer is a 1,4-cycloaddition reaction of a conjugated diene fatty acid and an anhydride containing a carbon-carbon double bond to generate a six-membered cyclic olefin. For example, conjugated linoleic acid, conjugated linoleic acid ethyl ester and maleic anhydride can be used. In some optional embodiments, the density of the drilling fluid system is 1.10g / cm 3 ~2.30g / cm 3 .

[0017] In some optional embodiments, the emulsifier is fatty acid polyamide;

[0018] The auxiliary emulsifier is a modified fatty acid amide;

[0019] The wetting agent is lauryl trimethyl ammonium bromide.

[0020] The second object of the present invention is to provide a drilling fluid system for improving the formation plugging and anti-collapse capability, comprising the following steps:

[0021] (1) Mix and stir the primary emulsifier, the auxiliary emulsifier, the wetting agent, the organic soil and the white oil;

[0022] (2) adding CaCl2 aqueous solution and quicklime and mixing;

[0023] (3) adding a filter loss reducer, an asphalt anti-collapse agent, and inorganic micro-nano particles and stirring at high speed to obtain a drilling fluid system;

[0024] The stirring speed in step (1) is 10000 r / min to 12000 r / min, and the stirring time is 20 min;

[0025] The stirring speed in step (2) is 10000 r / min to 12000 r / min, and the stirring time is 35 min;

[0026] The stirring speed in step (3) is 8000 r / min to 10000 r / min, and the stirring time is 60 min.

[0027] The third object of the present invention is to provide a drilling fluid system for improving the formation plugging and anti-collapse capability as described in any of the above items or the use of the drilling fluid system prepared by the above preparation method in oil drilling.

[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0029] (1) The drilling fluid system provided by the embodiment of the present invention improves the sealing and anti-collapse capability of the formation. The inorganic micro-nano particles of different particle sizes and the asphalt anti-collapse agent cooperate with each other to form a stable dense mud cake structure between the wellbore and the formation. For underground pores and cracks with a size range of 36nm-88μm, it can prevent the pressure from being transmitted to the cracks and increase the crack expansion resistance, thereby effectively improving the formation conditions. At the same time, the present invention strictly controls the content of each component so that the components can interact with each other so that the prepared drilling fluid can play the best effect during the drilling process, thereby enabling the prepared drilling fluid to improve the ability of the drilling fluid, prevent the well wall from collapsing and losing stability, and maintain the well wall stability, with good application effect.

[0030] (2) The drilling fluid system provided by the embodiment of the present invention improves the sealing and anti-collapse capability of the formation, and uses oxidized asphalt for anti-collapse, which can soften and deform under certain temperature and pressure. When under sufficiently high temperature and pressure, the asphalt is softened and squeezed into the micro-cracks or pores of the shale, bonding the shale together. The asphalt can also cover the surface of the shale to form a dense and tough film, which not only continues the percolation of the drilling fluid filtrate into the interior of the shale, but also plays an ideal barrier effect on the erosion of the drilling fluid flow, thereby sealing the cracks. The two asphalts can be mixed to greatly improve the sealing effect of the asphalt.

[0031] (3) A drilling fluid system for improving the sealing and anti-collapse capability of formations provided in an embodiment of the present invention can be used for drilling in mud shale formations. Without affecting the rheological properties of the drilling fluid, the compactness and sealing effect of the mud cake are improved, and the permeability of the mud cake is reduced. Since the formation of mud shale gas wells is shale containing organic matter and clay minerals, both water and oil will have an adverse effect on the stability of the mud shale, thereby causing the well wall to become unstable. The present invention can reduce the impact of the drilling fluid on the well wall during drilling, reduce block drop, and ensure the smooth implementation of horizontal drilling.

[0032] (4) A drilling fluid system for improving the plugging and anti-collapse capability of formations provided by an embodiment of the present invention can be used for micro-cracks corresponding to underground pores and seams with a size range of 36nm-88μm, and a filtration loss of 1.4 to 2.2ml under high temperature and high pressure conditions, with a minimum filtration loss of 1.4mm and a mud cake thickness of 2mm. Under the condition of a ceramic sand table with an pore size of 10μm, after plugging with the drilling filtration fluid obtained in an embodiment of the present invention, the amount of instantaneous loss at 0min and long-term loss at 30min are both 0ml, which can achieve a good plugging and anti-collapse effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0034] Figure 1 The following is a comparison chart of the results of sand table tests of the drilling fluid system 1# obtained by using an embodiment of the present invention and the existing drilling fluid system 2#. Figure 1 (a) corresponds to the drilling fluid system 1# of the present invention, Figure 1 (b) Corresponds to the existing drilling fluid system comparison 2#.

[0035] Figure 2 This is a diagram showing the drilling effect when the drilling fluid system 5# obtained by an embodiment of the present invention is used for daily maintenance. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0038] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings. In the absence of conflict, the embodiments and features in the embodiments of this application can be combined with each other.

[0039] Embodiment 1:

[0040] A drilling fluid system for improving the sealing and anti-collapse capability of formations is prepared according to the following method:

[0041] (1) 90 parts by weight of white oil were weighed, and 3 parts by weight of organic soil (specifically bentonite modified by alkyl quaternary ammonium salt) were added under low speed stirring at 600 r / min, followed by 3 parts by weight of primary emulsifier (fatty acid polyamide), 3 parts of auxiliary emulsifier (modified fatty acid amide), and 3 parts of wetting agent (methyl trimethyl ammonium bromide), and stirred at 12000 r / min for 20 min, and allowed to stand at room temperature to allow them to be fully dispersed.

[0042] (2) adding 15 parts of 25% CaCl2 aqueous solution and 3 parts of quicklime under high-speed stirring at 10000 r / min and stirring for 35 minutes;

[0043] (3) Add 3 parts of a loss reducer (specifically, a conjugated diene fatty acid and an anhydride containing a carbon-carbon double bond undergo a 1,4-cycloaddition reaction to generate a hexacyclic olefin), 5 parts of an asphalt anti-collapse agent, 6 parts of micro-nano rigid particles (the ratio of the three types of particles is 1:1.2:2), and add 110 parts of barite according to the required density, 8000 r / min, and stirring time for 60 minutes to obtain the drilling fluid.

[0044] Among them, the average particle size of the inorganic micro-nano particles I is 10μm, the average particle size of the inorganic micro-nano rigid particles II is 10μm, and the average particle size of the inorganic micro-nano rigid particles III is 1.3μm; the asphalt anti-collapse agent is a mixture of oxidized asphalt powder with a softening point of 120°C and oxidized asphalt powder with a softening point of 140°C in a weight ratio of 1:2, the asphalt content of the oxidized asphalt powder with a softening point of 120°C is 35%, and the gum content is 30%, the asphalt content of the oxidized asphalt powder with a softening point of 140°C is 55%, and the gum content is 20%.

[0045] The specific preparation process of the fluid loss reducer is: a fatty acid containing conjugated dienes (such as conjugated linoleic acid, conjugated linoleic acid ethyl ester, etc.) and an anhydride containing a carbon-carbon double bond (such as maleic anhydride, etc.) undergo a 1,4-cycloaddition reaction to generate a six-membered cyclic olefin.

[0046] The results of the high temperature and high pressure (HTHP) loss test and other performance tests of the drilling fluid are shown in Table 1.

[0047] Embodiment 2:

[0048] A drilling fluid system for improving the sealing and anti-collapse capability of formations is prepared according to the following method:

[0049] (1) 90 parts by weight of white oil were weighed, and 2.5 parts by weight of organic soil (bentonite modified by alkyl quaternary ammonium salt) was added under stirring at a low speed of 600 r / min, followed by 5 parts by weight of primary emulsifier (fatty acid polyamide), 2.5 parts of auxiliary emulsifier (modified fatty acid amide), and 3 parts of wetting agent (methyl trimethyl ammonium bromide). The mixture was stirred at 12000 r / min for 20 min, and allowed to stand at room temperature to allow it to be fully dispersed.

[0050] (2) adding 10 parts of 25% CaCl2 aqueous solution and 3 parts of quicklime under high-speed stirring at 10000 r / min and stirring for 35 minutes;

[0051] (3) Add 5 parts of a loss reducer (containing a conjugated diene fatty acid and an anhydride containing a carbon-carbon double bond to undergo a 1,4-cycloaddition reaction to generate a six-membered cycloolefin), 4.5 parts of an asphalt anti-collapse agent, 2 parts of micro-nano rigid particles (the ratio of the three types of particles is 1:1.2:2), and 15 parts of barite according to the required density, 8000 r / min, and stirring time for 60 minutes to obtain the drilling fluid.

[0052] Among them, the average particle size of the inorganic micro-nano particles I is 53μm, the average particle size of the inorganic micro-nano rigid particles II is 6.5μm, and the average particle size of the inorganic micro-nano rigid particles III is 13μm; the asphalt anti-collapse agent is a mixture of oxidized asphalt powder with a softening point of 130°C and oxidized asphalt powder with a softening point of 150°C in a weight ratio of 1:2, the asphalt content of the oxidized asphalt powder with a softening point of 130°C is 40%, and the gum content is 32%, the asphalt content of the oxidized asphalt powder with a softening point of 150°C is 40%, and the gum content is 35%.

[0053] The specific preparation process of the fluid loss reducer is the same as that of Example 1.

[0054] The results of the high temperature and high pressure (HTHP) loss test and other performance tests of the drilling fluid are shown in Table 1.

[0055] Embodiment 3:

[0056] A drilling fluid system for improving the sealing and anti-collapse capability of formations is prepared according to the following method:

[0057] (1) 90 parts by weight of white oil were weighed, and 4 parts by weight of organic soil were added under low-speed stirring at 600 r / min, followed by 5 parts by weight of primary emulsifier (fatty acid polyamide), 4 parts of auxiliary emulsifier (modified fatty acid amide), and 3 parts of wetting agent (methyltrimethylammonium bromide), and stirred at 12000 r / min for 20 min, and allowed to stand at room temperature to allow them to be fully dispersed.

[0058] (2) adding 20 parts of 25% CaCl2 aqueous solution and 4 parts of quicklime under high-speed stirring at 10000 r / min and stirring for 35 minutes;

[0059] (3) Add 4 parts of loss reducer, 6 parts of asphalt anti-collapse agent, 8 parts of micro-nano rigid particles (the ratio of the three kinds of particles is 1:1.2:2), and add 60 parts of barite according to the required density, 8000r / min, and stir for 60min to obtain the drilling fluid.

[0060] Among them, the average particle size of the inorganic micro-nano particles I is 35μm, the average particle size of the inorganic micro-nano rigid particles II is 12μm, and the average particle size of the inorganic micro-nano rigid particles III is 8.5μm; the asphalt anti-collapse agent is a mixture of oxidized asphalt powder with a softening point of 140°C and oxidized asphalt powder with a softening point of 160°C in a weight ratio of 1:2, the asphalt content of the oxidized asphalt powder with a softening point of 140°C is 38%, and the gum content is 35%, the asphalt content of the oxidized asphalt powder with a softening point of 160°C is 50%, and the gum content is 30%.

[0061] The specific preparation process of the fluid loss reducer is the same as that of Example 1.

[0062] The results of the high temperature and high pressure (HTHP) loss test and other performance tests of the drilling fluid are shown in Table 1.

[0063] Embodiment 4:

[0064] The drilling fluid was prepared in the same manner as in Example 1, except that the inorganic micro-nano rigid particles I, II, and III used in Example 1 were mixed in a ratio of 1:1:1. The drilling fluid sample was subjected to a HTHP water loss test, and the results are shown in Table 1.

[0065] The specific preparation process of the fluid loss reducer is the same as that of Example 1.

[0066] Comparative Example 1:

[0067] The drilling fluid was prepared in the same manner as in Example 1, except that the inorganic micro-nano rigid particles I, II, and III used in Example 1 were mixed in a ratio of 2:1:1. The drilling fluid sample was subjected to a HTHP water loss test, and the results are shown in Table 1.

[0068] Comparative Example 2:

[0069] The drilling fluid was prepared in the same manner as in Example 1, except that the inorganic micro-nano rigid particles I, II, and III used in Example 1 were mixed in a ratio of 1:0:1. The drilling fluid sample was subjected to a HTHP water loss test, and the results are shown in Table 1.

[0070] Comparative Example 3:

[0071] The drilling fluid was prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent used in Example 1 was reduced to 2.5 parts. The drilling fluid sample was subjected to a HTHP water loss test, and the results are shown in Table 1.

[0072] Comparative Example 4

[0073] The drilling fluid was prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent used in Example 1 was reduced to 0 parts by weight. The drilling fluid sample was subjected to a HTHP water loss test, and the results are shown in Table 1.

[0074] Comparative Example 5:

[0075] The drilling fluid was prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent used in Example 1 was increased to 8 parts. The drilling fluid sample was subjected to a HTHP water loss test, and the results are shown in Table 1.

[0076] Comparative Example 6:

[0077] The drilling fluid was prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent used in Example 1 was a mixture of oxidized asphalt powder having a softening point of 120°C and oxidized asphalt powder having a softening point of 170°C.

[0078] Comparative Example 7:

[0079] The drilling fluid is prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent used in Example 1 is a mixture of oxidized asphalt powder having a softening point of 100°C and oxidized asphalt powder having a softening point of 140°C.

[0080] Comparative Example 8:

[0081] The drilling fluid is prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent with a softening point of 120°C used in Example 1 has an asphalt content of 20% and a colloid content of 20%, and the oxidized asphalt powder with a softening point of 140°C has an asphalt content of 55% and a colloid content of 20%.

[0082] Comparative Example 9:

[0083] The drilling fluid is prepared in the same manner as in Example 1, except that the asphalt anti-collapse agent with a softening point of 120°C used in Example 1 has an asphalt content of 35% and a colloid content of 30%, and the oxidized asphalt powder with a softening point of 140°C has an asphalt content of 65% and a colloid content of 10%.

[0084] Table 1 Drilling fluid properties under various embodiments

[0085]

[0086] From the above data, it can be seen that the filtration loss of the drilling fluid of Examples 1-4 under high temperature and high pressure (150°C, 4.2MPa pressure) is between 1.4 and 2.2ml. Under the optimal formulation, the minimum filtration loss is 1.4ml and the thickness of the mud cake is 2.0mm.

[0087] Comparing Example 1 with Comparative Examples 1 and 2, when the weight ratio of the inorganic micro-nano rigid particles I, II, and III exceeds the range of 1:1-2:1-3, the filtration loss increases, the mud cake thickness increases to 2.5 mm, and the plugging effect is not as good as that of Examples 1-4. It can be seen that when the amount of oxidized asphalt is satisfied, the ratio of inorganic micro-nano rigid particles of different particle sizes will also affect the filtration effect. In the process of water loss and wall building of the drilling fluid, the inorganic micro-nano rigid particles I, II, and III are matched through reasonable ratio and particle size, and the particles are squeezed against each other, tightly combined, and alternately plugged, forming a denser and tougher mud cake, which effectively improves the pressure bearing capacity of the formation.

[0088] When comparing Example 1 with Comparative Examples 3 and 5, when the weight of the asphalt anti-collapse agent exceeds the range of 4.5 to 6, the filtration loss is significantly higher than that of Example 1, and the thickness of the mud cake also increases. When comparing Example 1 with Comparative Example 4, when there is no asphalt anti-collapse agent, the water loss will increase due to the lack of effective coordination of inorganic micro-nano rigid particles and the asphalt anti-collapse agent. This shows that the asphalt anti-collapse agent has an excellent bridging effect, and the effect of reducing filtration loss is achieved through sufficient filling of inorganic ions.

[0089] When comparing Example 1 with Examples 6, 7, 8, and 9, when the softening point of the oxidized asphalt powder of the asphalt anti-collapse agent is lower or higher than the preferred value, it will lead to thickening of the drilling fluid, increased water loss, and thickening of the mud cake. This is because the softening point of the asphalt is not selected correctly, resulting in failure to soften at this temperature, increased water loss, and water loss distribution between 3.2 and 4.0 ml.

[0090] It can be seen that only by using appropriate components and proportions can a dense mud cake be formed on the well wall, strengthening the well wall, reducing fluid invasion into the formation, and thus improving the anti-collapse ability of the formation.

[0091] In summary, the present invention uses a combination of oxidized asphalt and rigid plugging materials of different particle sizes to plug different microcracks and holes in the shale through a synergistic plugging effect, forming a thin and tough mud cake with good loss-proof wall-building properties, preventing the penetration of drilling fluid filtrate into the shale, thereby stabilizing the well wall and achieving the purpose of rapid drilling.

[0092] Application examples:

[0093] Case 1:

[0094] The longitudinal profile of unfractured shale of the Longmaxi Formation was measured, and the sizes of pores and fractures ranged from 104nm to 244μm. The proportional coefficient of the in-situ and surface decompression of the bedding fracture size at a depth of 2500m was about 0.36, corresponding to the underground pore and fracture size range of 36nm-88μm. Therefore, in order to reduce the impact of the drilling fluid on the well wall, the micron-level plugging effect can be used to evaluate the plugging ability of the drilling fluid system provided in the embodiment of the present invention.

[0095] Take 4 longitudinal profile samples of unfragmented shale of the Longmaxi Formation in adjacent blocks, respectively adopt the drilling fluid system of Example 1 of the present invention (as 1#), adopt the existing commercially available drilling fluids Comparison 1#, Comparison 2#, Comparison 3# (Comparison 2#, 3#, 4# drilling fluids were purchased from Western Drilling Company, Beacon Drilling Company, and Jianghan Drilling Company, respectively), and conduct plugging tests on the obtained 4 samples. The drilling fluid plugging performance evaluation instrument PPA was used in this plugging experiment, and a ceramic sand tray with a minimum of 10μm was used to evaluate the plugging effect of a 10μm pore size. Four portions of oil-based drilling fluid were hot-rolled at 150°C for 16 hours, and stirred at high speed for 10 minutes after cooling. A ceramic sand tray with a pore size of 10μm (3μm for gas measurement and 10μm for mercury injection) was used for PPA filtering. The experimental results are shown in Table 2, and as shown in the attached figure. Figure 1 shown.

[0096] Table 2 10 micron sand table test results

[0097]

[0098]

[0099] It can be seen from the experimental results that, under the condition of a ceramic sand tray with an pore size of 10 μm, after plugging with the drilling filtration fluid of Example 1, the amount of loss at 0 min (instantaneous loss) and 30 min (long-term loss) is the minimum of 0 ml, indicating that the drilling fluid system of Example 1 has the best plugging effect on pores of 10 μm, and can achieve the purpose of plugging and preventing collapse. However, after plugging with the drilling fluid systems of Test Examples 2, 3, and 4, the amount of loss at 0 min (instantaneous loss) and 30 min (long-term loss) is significantly greater than the filtration loss of Example 1. It can also be seen from the test results of HTH water loss and HTHP mud cake that the drilling fluid system of Example 1 has the best plugging effect on pores of 10 μm, and can achieve the purpose of plugging and preventing collapse.

[0100] Case 2:

[0101] Well 201HX-Y is a horizontal well for shale gas development. Its structural location is the Weiyuan block in the Sichuan Basin, and its geographical location is Rong County, Zigong City. The designed well depth is 6650m, the designed vertical depth is 3659m, and the target layer is the Longmaxi Formation. Well 201HX-Y was opened on March 2, 2023 and the oil-based drilling fluid of the present invention was used. The drilling fluid formula 5# (an embodiment of the present invention) used is: 90 parts of white oil + 3 parts of primary emulsifier + 3 parts of auxiliary emulsifier + 3.5 parts of wetting agent + 3 parts of organic soil + 3 parts of filtration reducer + 2.5 parts of quicklime + 6 parts of inorganic micro-nano particles (Ⅰ, Ⅱ, Ⅲ) + 4.5 parts of asphalt anti-collapse agent + 15 parts of 25% calcium chloride brine, weighted with barite to the required density of 2.10g / cm 3 .

[0102] The above-mentioned drilling fluid system 5# is used for daily drilling fluid maintenance in Well 201HX-Y. The drilling fluid properties are shown in Table 3.

[0103] From the drilling effect, the horizontal section was drilled smoothly without any jamming, and there was no abnormal fluctuation in torque and hanging weight. Figure 2 . Working with other drilling teams to drill wells in the same area, the drilling cycle was saved by 5 to 10 days, achieving the goal of high quality and speed.

[0104] Table 3 Performance of drilling fluid system 5# in the horizontal section of Longmaxi Formation in Well 201HX-Y

[0105]

[0106] Analysis of Table 3 shows that under this formula, the drilling fluid performance is stable, water loss is controlled at 1.6-2.0 ml, the mud cake is normal, and the rheology of the drilling fluid is normal. During the drilling process, the friction resistance of the drill bit is normal, and the wellbore is smooth without falling blocks.

[0107] In summary, the present invention provides a drilling fluid system for improving the plugging and anti-collapse ability of formations. By using a good loss reducer, an asphalt anti-collapse agent and plugging materials of different particle sizes in combination, a dense mud cake is formed on the surface of the rock formation, which effectively prevents the liquid phase in the drilling fluid from penetrating into the formation, thereby improving the stability of the well wall, reducing block falling, and ensuring smooth completion.

[0108] It should be noted that:

[0109] (1) The “portions” mentioned in the above embodiments, comparative examples and application cases may be weight units of g or kg.

[0110] (2) Unless otherwise specified, the materials used in the above embodiments, comparative examples and application cases can be common commercially available products.

[0111] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A drilling fluid system for improving the ability of formation plugging and anti-collapse, characterized in that: The invention comprises the following components in parts by weight: 90 parts of white oil, 10 to 20 parts of CaCl2 salt water, 2.5 to 4 parts of organic soil, 3 to 5 parts of emulsifier, 2.5 to 4 parts of auxiliary emulsifier, 3 to 5 parts of fluid loss reducer, 2.5 to 4 parts of wetting agent, 2.5 to 4 parts of quicklime, 2 to 8 parts of inorganic micro-nano particles, 4.5 to 6 parts of asphalt anti-collapse agent, and 15 to 110 parts of barite; The inorganic micro-nano particles include inorganic micro-nano particles I, inorganic micro-nano particles II, and inorganic micro-nano particles III. The average particle size of the inorganic micro-nano particles I is 10 μm to 53 μm, the average particle size of the inorganic micro-nano rigid particles II is 6.5 μm to 18 μm, and the average particle size of the inorganic micro-nano rigid particles III is 1.3 μm to 13 μm.

2. A drilling fluid system for improving formation plugging and anti-collapse capability according to claim 1, characterized in that: The weight ratio of the inorganic micro-nano particles I, the inorganic micro-nano rigid particles II, and the inorganic micro-nano rigid particles III is 1:1-2:1-3.

3. A drilling fluid system for improving formation plugging and anti-collapse capability according to claim 1, characterized in that: The weight ratio of the inorganic micro-nano particles I, the inorganic micro-nano rigid particles II, and the inorganic micro-nano rigid particles III is 1:1.2:2; The inorganic micro-nano particles are calcium carbonate particles.

4. A drilling fluid system for improving formation plugging and anti-collapse capability according to claim 1, characterized in that: The asphalt anti-collapse agent is a mixture of oxidized asphalt powder with a softening point of 120°C to 140°C and oxidized asphalt powder with a softening point of 140°C to 160°C; The asphalt content of the oxidized asphalt powder with a softening point of 120°C to 140°C is 35% to 40%, and the colloid content is 30% to 35%. The asphalt content of the oxidized asphalt powder with a softening point of 140°C to 160°C is 40% to 55%, and the colloid content is 20% to 35%.

5. A drilling fluid system for improving formation plugging and anti-collapse capability according to claim 4, characterized in that: The oxidized asphalt powder with a softening point of 120°C to 140°C and the oxidized asphalt powder with a softening point of 140°C to 160°C are mixed in a mass ratio of 1:

2.

6. A drilling fluid system for improving formation plugging and anti-collapse capability according to claim 1, characterized in that: The fluid loss reducer comprises a modified fatty acid fluid loss reducer, and the modified fatty acid fluid loss reducer is a fluid loss reducer synthesized by using a diene synthesis reaction with fatty acid and anhydride as monomers.

7. A drilling fluid system for improving formation plugging and anti-collapse capability according to claim 1, characterized in that: The density of the drilling fluid system is 1.10 g / cm 3 ~2.30g / cm 3 .

8. The drilling fluid system for improving the formation plugging and anti-collapse capability according to claim 1, characterized in that: The emulsifier is fatty acid polyamide; The auxiliary emulsifier is a modified fatty acid amide; The wetting agent is lauryltrimethylammonium bromide.

9. A method for preparing a drilling fluid system for improving formation plugging and anti-collapse capabilities according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Mix and stir the primary emulsifier, the auxiliary emulsifier, the wetting agent, the organic soil and the white oil; (2) adding CaCl2 aqueous solution and quicklime and mixing; (3) adding a filter loss reducer, an asphalt anti-collapse agent, inorganic micro-nano particles, and barite, and stirring at high speed to obtain a drilling fluid system; The stirring speed in step (1) is 10000 r / min to 12000 r / min, and the stirring time is 20 min; The stirring speed in step (2) is 10000 r / min to 12000 r / min, and the stirring time is 35 min; The stirring speed in step (3) is 8000 r / min to 10000 r / min, and the stirring time is 60 min.

10. Use of the drilling fluid system for improving the formation plugging and anti-collapse capability according to any one of claims 1 to 8 or the drilling fluid system prepared by the preparation method according to claim 9 in oil drilling.